(untitled) (Materiali di Estetica. Terza serie, 2020)
The aim of the present essay is to offer a presentation of the personality and thought of Dino Formaggio in order to highlight “Doing” as the pivotal moment of his aesthetics. Doing is rooted in the sensitive world, in the body, which is a source of energy and requires an ex-pression of the Self from within. The different spheres in which Formaggio’s “Doing” is articulated are first of all creativity in painting, sculpture, poetry but we have also to consider his non-passive view of nature alongside with teaching as a product of effective human relationships. The present contibution investigates hence Formaggio’s artistic fruition which entails a non-contemplative, active vision: seeing, listening, understanding cannot be considered passively. Far from being unreceptive, the act of seeing implies an active involvement of the senses which leads to action, practising and commitment: reality, the environment, the others are invested by this form of Doing. And this happens at various levels ranging from remake of other people’s works for oneself (a Kandinsky, the Scribe of the Louvre) to historical understanding of art up to personal reflection. We can therefore maintain that for Dino Formaggio thinking about art from a philosophical perspective stems from doing, in this “Doing” it must occur and in a “Doing” it must flow and pour the essence of individual and social possibilities.